2018
DOI: 10.1371/journal.pmed.1002578
|View full text |Cite|
|
Sign up to set email alerts
|

The state of the antivaccine movement in the United States: A focused examination of nonmedical exemptions in states and counties

Abstract: In a Policy Forum, Peter Hotez and colleagues discuss vaccination exemptions in US states and possible consequences for infectious disease outbreaks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
136
0
12

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(148 citation statements)
references
References 9 publications
0
136
0
12
Order By: Relevance
“…Folowing the analysis of Olive et al [10], we expected a negative association between nonmedical exemptions and school-aged children vaccination levels. We extended their analysis for 2016-2017 to all states (irrespective of the breadth of the non-medical exemptions they allow) and found that higher rates of non-medical exemptions are associated with lower vaccination rates for the MMR vaccine (Figure 1A; beta regression ; p < 0.001).…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Folowing the analysis of Olive et al [10], we expected a negative association between nonmedical exemptions and school-aged children vaccination levels. We extended their analysis for 2016-2017 to all states (irrespective of the breadth of the non-medical exemptions they allow) and found that higher rates of non-medical exemptions are associated with lower vaccination rates for the MMR vaccine (Figure 1A; beta regression ; p < 0.001).…”
Section: Resultsmentioning
confidence: 88%
“…This association, along with the heterogeneous spatial distribution of non-medical exemptions, creates pockets of eroded herd immunity where outbreaks of vaccine preventable diseases would be more likely [30]. Furthermore, we illustrate that this is true not only for MMR [10] but for a wide range of childhood diseases. It is thus important to consider the compounded risk of all childhood diseases when evaluating the public health risk posed by non-medical exemptions.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…27 Several US metropolitan areas represent "hot spots" for these exemptions. 28 This may render such areas vulnerable to vaccine-preventable diseases, including infl uenza.…”
Section: How Effective Is It?mentioning
confidence: 99%
“…I think I know most of it anyway." Oder auch die zunehmende Impfverweigerung aufgrund medizinisch nicht begründeter Vorbehalte [5]. Über ein Drittel der Laien nimmt an, mehr über Ursachen von Autismus zu wissen als Ärzte oder Wissenschaftler.…”
unclassified